KAJIAN EFISIENSI PADA KELOMPOK TIANG DENGAN KONFIGURASI 3 X 3 - Azami, Fikri Irfanil; Priadi, Eka; Bachtiar, Vivi (Jurnal Mahasiswa Teknik Sipil Universitas Tanjungpura, 2017)
The condition of soil is the most important to be identified in planning and constructing a construction on it. Soil condition in West Kalimantan, especially in the city of Pontianak in general is the form of soft soil and its surface layer contains organic materials as a result of weathering wood and soil with a better carrying capacity can only be found at a depth of 30-40 meters. To overcome the poor condition of soil carrying capacity, the early works must be done to improve soil bearing capacity, the thing that is often used in Pontianak is using pile.The possibility of a construction consisting of a single pile is very rare, generally at least two or more piles are fitted under the pile cap of the foundation. The number possessed by those group of piles has different efficiency values, because the number of piles affect the efficiency of the pile group.In this test the testing preparation testing of pile group loading with the same configuration and number of piles with different pile distance will be done, the distance of 3D and 4D will be used. Differences in the distance between the piles in the pile group were done to determine the effect of the distance between the piles on the efficiency of the pile group.From the test results, it is known that the difference in pile distance in a group of piles affects the efficiency of a pile group. The results of 3D pile group loading have smaller efficiency than the pile group with 4D distance. This is because the factor of stress spreading around the overlapping pile will be smaller if the distance of the pile is greater